Effect Of Post-Hatch Delay In Feeding On Performance And Blood Biochemistry Of Chabro Chicken (Applied Biological Research, 2017)
In Kashmir, a large number of 1-day old chicks are procured from  neighbouring states which puts birds to early life stress during  transportation and affects their growth performance. The present study  was aimed to evaluate the role of different durations of post-hatch delay in  feeding in Chabro chicken. Four hundred 1-day old Chabro chicks were  randomly divided into 5 groups with 4 replicates of 20 birds each and  subjected to different durations of delay in post-hatch delay feeding for 6  weeks. Control chicks were offered feed at hatchery while in other groups  feeding was started after delay of 12, 24, 48 and 72 h. As the post-hatch  feeding was delayed at the start of experiment, it caused a significant  (P
Keywords: Blood biochemistry; Chabro chick; delayed feeding; performance